The research journal TRANSPORT: peer-reviewing process in 2013 - Prentkovskis, Olegas; Junevičius, Raimundas (Transport, 2013)
„The research journal TRANSPORT: peer-reviewing process in 2013" Transport, 28(4), p. 438-442First Published Online: 24 Dec 2013